CFO Characteristics and Accounting Conservatism in Indonesia - Amalia, Annisa Puspita; Suryani, Ani Wilujeng; Sulistyawati, Septy Nur (Universitas Negeri Malang, 2025)
The Chief Financial Officer (CFO) tends to ignore accounting conservatism when deal with financial uncertainty. This encourages CFOs to take high-risk decisions that can be detrimental to the company. The implementation of accounting conservatism is influenced by individual characteristics such as gender, age, level of education, and tenure. Therefore, this study aims to determine the effect of CFO characteristics on accounting conservatism. This study was conducted on 80 companies from the energy, transportation and logistics, and food and beverage sectors listed on the Indonesia Stock Exchange from 2018 to 2021. The hypothesis was tested using Generalized Least Square (GLS) regression. The result showed that age and educational level had a positive effect on accounting conservatism, while gender and tenure did not. Thus, company management should consider the age and level of education of prospective executives to improve the quality of company financial decisions. Previous research related to CFO characteristics and accounting conservatism has been conducted in developed countries, while this research uses the context of a developing country, namely Indonesia. Even though the applicable Financial Accounting Standards already contain regulations that apply the principle of accounting conservatism, companies in Indonesia tend not to be conservative.